2020
DOI: 10.3390/catal10080834
|View full text |Cite
|
Sign up to set email alerts
|

Entrapping Immobilisation of Lipase on Biocomposite Hydrogels toward for Biodiesel Production from Waste Frying Acid Oil

Abstract: A new application of biocomposite hydrogels named gelatin-alginate (GA) and pectin alginate (PA) enables the use of the hydrogels as carriers for lipase entrapment during biodiesel production. Waste frying acid oil (WFAO), a raw material, was converted to biodiesel via an esterification reaction catalysed by two different immobilised biocatalysts: gelatin-alginate lipase (GAL) and pectin-alginate lipase (PAL). The highest immobilisation yield of GAL and PAL beads was achieved at 97.61% and 98.30%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
(50 reference statements)
2
8
0
Order By: Relevance
“…1 ). Gel–Alg and CAT–Gel–Alg reached a maximum absorption value of 660% and 674%, respectively, after 3 h. Similarly, Muanruksa et al ( 2020 ) reported that the prepared alginate hydrogel absorbed a greater amount of water, as the retention time increased till an equilibrium status was reached (3 h). These results are an indication of the ability of the hydrogel to prevent the accumulation of wound fluid by absorbing the exudates for effective wound dressing.…”
Section: Resultsmentioning
confidence: 82%
“…1 ). Gel–Alg and CAT–Gel–Alg reached a maximum absorption value of 660% and 674%, respectively, after 3 h. Similarly, Muanruksa et al ( 2020 ) reported that the prepared alginate hydrogel absorbed a greater amount of water, as the retention time increased till an equilibrium status was reached (3 h). These results are an indication of the ability of the hydrogel to prevent the accumulation of wound fluid by absorbing the exudates for effective wound dressing.…”
Section: Resultsmentioning
confidence: 82%
“…Different hybrid supports based on pectin were described for enzyme encapsulation, such as a pectin/alginate [ 92 , 93 , 94 ], pectin/poly-vinyl alcohol [ 95 ], pectin/chitosan [ 96 ], carrageenan/pectin [ 75 ], and pectin/pine fiber [ 97 ]. The pectin combination with other polymers improves some key properties, such as mechanical and thermal resistances.…”
Section: Most Used Polymers For Enzyme Encapsulationmentioning
confidence: 99%
“…Microbial lipase is also important because it is easy to ferment and purify and thus presents itself as one of the most common sources for biodiesel production through transesterification [4]. However, the utilization of free lipase may carry some disadvantages such as high cost, low stability and long reaction time [5]. Therefore, lipase immobilisation on suitable support is the key parameter to achieve enhanced stability, reusability, easy product separation and recovery, reduced cost for lipase production and improved control of reactions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among the four immobilization techniques namely entrapment, physical adsorption, covalent binding and cross-linking, the entrapment technique emerged as the most beneficial approach since this technique is straightforward, requires low cost of operation, can be performed under mild reaction conditions, high recovery of activity and allows effortless diffusion of substrates through the immobilization matrix pore [5]. In addition, the entrapment technique does not use physical force and chemical reaction and by this means supports stable enzyme conformation for a longer period of time [5]. The utilization of hydrogels in particular to immobilize the enzyme offers many benefits such as the ability to absorb water and swell readily without dissolving and sustaining the three-dimensional structure of enzyme [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation